Frequency and outcomes of STEMI patients presenting between 12 and 24 h after symptom onset: Late‐presenting STEMI. Issue 1 (24th November 2022) - Griffin, Anna C. Gonzalez; Yildiz, Mehmet; Bradley, Steven; Smith, Jenna E.; Garcia, Santiago; Schmidt, Christian W.; Garberich, Ross; Walser‐Kuntz, Evan; Traverse, Jay; Jollis, James G.; Sharkey, Scott W.; Henry, Timothy D.
Abstract: Objectives: To assess the characteristics and prognosis of ST‐elevation myocardial infarction (STEMI) patients, presenting between 12 and 24 h after symptom onset, in contemporary regional STEMI systems of care in the United States. Background: Previous observational studies have been inconsistent regarding the benefit of primary percutaneous coronary intervention (PCI) compared with conservative management for late‐presenting STEMI patients and the majority of randomized trials are from the fibrinolytic era. Methods: Using a two‐center registry‐based cohort from March 2003 to December 2020, we evaluated the frequency, clinical characteristics, and outcomes of STEMI patients, stratified by symptom onset to balloon time: <3, 3−6, 6−12, and 12−24 h (late presenters). Results: Among 5427 STEMI patients with available symptom onset time, 6.2% were late presenters, which increased to 11% during the early phase of the Covid‐19 pandemic. As symptom onset to balloon time increased, patients were more likely to be older, female, and have a history of hypertension and diabetes mellitus. Late presenters with an identifiable culprit lesion were less likely to be revascularized with PCI (96%, 96%, 95%, and 92%; p for trend = 0.004) and had a longer median door‐to‐balloon time (82, 109, 107, and 117 min; p for trend < 0.001). In‐hospital and 1‐year death risks were comparable between late and earlier presenters. Conclusion: Despite the unfavorable risk profile and longer door‐to‐balloon time, clinical outcomes of late presenters were similar to those presenting within 12 h of symptom onset.